Consumer engagement on Twitter: perceptions of the brand matter. (9th September 2019) - Read, Wayne; Robertson, Nichola; McQuilken, Lisa; Ferdous, Ahmed Shahriar
Abstract : Purpose: This paper aims to develop and empirically test a theoretical framework of consumer engagement with brands on Twitter. Design/methodology/approach: Depth interviews were conducted to gain initial insights into consumer engagement on Twitter. Using a blend of the extant literature and interview findings, a theoretical framework, including antecedents, outcomes and moderators, was developed and empirically tested using cross-sectional survey data. Findings: Brand customer service and brand intimacy positively influence consumer engagement on Twitter, and consumer engagement mediates the relationship between these antecedents and consumer co-promotion intentions. Consumer perceptions of a brand account's popularity on Twitter and their likelihood of adding value to a brand are found to be moderators within the conceptual framework. Research limitations/implications: Caution needs to be exercised in generalising these findings beyond the Twitter context, and the use of a cross-sectional survey means causality cannot be inferred. Practical implications: Brands need to be perceived as providing excellent customer service and intimate brand knowledge on Twitter to drive consumer engagement and co-promotion. Brands are recommended to develop strategies to increase their Twitter following, including rewarding consumers for their contributions on the brand's Twitter account to signal that they are valued. Originality/value: The authors add to the emerging literature on consumer engagement on social media in two key ways, by developing and testing a theoretical framework of consumer engagement in the Twitter context and by identifying moderators in the consumer engagement process on Twitter.